there are no innocent spaces (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This processes reflects on the relations between social imagination and the processual configuration of space. It asks how ideological and imaginary spaces are intertwined in the construction of concrete empirical spaces that materialize the rules of social connectitivity and separation. It reflects on how unfinished spaces and knowledges contribute to fixed social relation in the sense of immobilizing the reflection by focusing it somewhat obsessively on the threatening lack that this formal unfinishedness incarnates.
Keywords: Social space; Ideological space; Social and spatial perception